Combined effects of microencapsulated essential oils and irradiation from gamma and X-ray sources on microbiological and physicochemical properties of dry fermented sausages during storage. (1st April 2022) - Ji, Jiali; Allahdad, Zahra; Sarmast, Elham; Salmieri, Stephane; Lacroix, Monique
Abstract: Essential oils (EOs) or EOs encapsulated in alginate and alginate-cellulose nanocrystal combined with 1.5 kGy X-ray (0.76 kGy/h) or γ-ray (6.37 kGy/h) irradiation were applied on dry fermented sausages (DFS). Microbiological quality was tested in terms of the reduction of Escherichia coli O157:H7 cocktail, Listeria monocytogenes, molds and yeasts, lactic acid bacteria (LAB), and total mesophilic bacteria (TMF) during storage at room temperature (20 ± 1 °C) for 8 weeks. Physicochemical quality was tested by following the changes of texture and color of sausages. Synergistic effects were observed with combined treatments with γ-irradiation on inhibiting E. coli O157:H7 cocktail and LAB and with X-ray on inhibiting E. coli O157:H7 cocktail. Extensive inhibition of L. monocytogenes, molds and yeasts, and TMF was also noticed during storage. Antimicrobial formulations combined with γ-irradiation did not show adverse effects on texture and color of sausages while treatment with X-ray resulted in the reduction of redness and increase of hardness. However, the differences of texture were eliminated during storage. Highlights: Essential oils (EOs) were microencapsulated (ME) in Alginate or Alginate-CNC. Free and ME EOs, X-irradiation, and γ-irradiation had strong antimicrobial effects. XI hardened the texture initially and the effect decreased during storage. XI reduced exterior and interior redness but reduction was moderated over time.